2001
DOI: 10.1093/ajcn/74.4.449
|View full text |Cite
|
Sign up to set email alerts
|

Moderate intake of n−3 fatty acids is associated with stable erythrocyte resistance to oxidative stress in hypertriglyceridemic subjects

Abstract: Although they exhibit a high susceptibility to oxidation, n-3 fatty acids may preserve membrane integrity and represent an added benefit in the treatment of hypertriglyceridemic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…In addition, docosahexaenoic acid, one of the n-3 HUFA, affects the fluidity and rigidity of the cell membrane structure [27]. Previous studies have also suggested that stability of erythrocytes is related to the n-3 HUFA content in the biomembrane of erythrocytes [28][29][30]. Digestive absorption of lipid is promoted with bile acid, and bile acid conjugates with glycine and/or taurine prior to secretion [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, docosahexaenoic acid, one of the n-3 HUFA, affects the fluidity and rigidity of the cell membrane structure [27]. Previous studies have also suggested that stability of erythrocytes is related to the n-3 HUFA content in the biomembrane of erythrocytes [28][29][30]. Digestive absorption of lipid is promoted with bile acid, and bile acid conjugates with glycine and/or taurine prior to secretion [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to LDL in vitro oxidation, another measure of overall antioxidant defense based on the susceptibility of erythrocytes to free radical-induced hemolysis has been set up and used under various clinical and experimental conditions (5,22,32).…”
Section: Introduction E Xperimental and Clinical Studies Have Documentedmentioning
confidence: 99%
“…Reactive oxygen species (ROS) generated in the plasma, cytosol, or cell membrane can attack erythrocyte membranes, compromise their integrity, and induce the oxidation of lipids and protein resulting in hemolysis (Bracci et al 2002, Chan et al 1999, Delmas-Beauvieux et al 1995, Niki et al 1988. Given their function, and their susceptibility to oxidative damage, investigators have used erythrocytes, and free radical initiators such as 2,2 0 -azo-bis (2-amidinopropane) dihydrochloride (AAPH) and UVB as models for studying biomembrane oxidative damage (Carini et al 2000, Chan et al 1999, Liu et al 2002, Mabile et al 2001, Niki et al 1988, Zhu et al 2002. We recently studied the inhibitory effects of flavanoid-rich cocoa extract on rat erythrocyte hemolysis, and found that hemolysis resistance was enhanced following the feeding of this extract ðp , 0:05Þ (Zhu et al 2002).…”
Section: Introductionmentioning
confidence: 99%